Exercise-Induced Improvements in Insulin Sensitivity Are Not Attenuated by a Family History of Type 2 Diabetes - Amador, Manuel; Meza, Cesar A.; McAinch, Andrew J.; King, George A.; Covington, Jeffrey D.; Bajpeyi, Sudip (Frontiers in Endocrinology, 2020)
Introduction: A family history of diabetes (FH+) is a major risk factor for the development of insulin resistance and type 2 diabetes. However, it remains unknown whether exercise-induced improvements in insulin sensitivity and metabolic flexibility are impacted by a FH+. Therefore, we investigated whether improvements in insulin sensitivity, metabolic flexibility, body composition, aerobic fitness and muscle strength are limited by a FH+ following eight weeks of combined exercise training compared to individuals without a family history of type 2 diabetes (FH-). Methods: Twenty (n = 10 FH-, n = 10 FH+) young, healthy, sedentary, normoglycemic, Mexican-American males (age: FH- 22.50 ± 0.81, FH+ 23.41 ± 0.86 years; BMI: FH- 27.91 ± 1.55, FH+ 26.64 ± 1.02 kg/m2) underwent eight weeks of combined aerobic and resistance exercise training three times/week (35-min aerobic followed by six full-body resistance exercises). Insulin sensitivity was assessed via hyperinsulinemic euglycemic clamps. Metabolic flexibility was assessed by the change in respiratory quotient from fasted to insulin-stimulated states. Body composition was determined using dual-energy x-ray absorptiometry. Aerobic fitness was determined by a graded exercise test, and upper- and lower-body strength were assessed via one-repetition maximum bench press and leg strength dynamometer, respectively. Results: Insulin sensitivity, metabolic flexibility, aerobic fitness and strength were not different between groups (p > 0.05). Eight weeks of combined aerobic and resistance exercise training improved insulin sensitivity (FH- p = 0.02, FH+ p = 0.002), increased fat free mass (FH- p = 0.006, FH+ p = 0.001), aerobic fitness (FH- p = 0.03, FH+ p = 0.002), and upper- (FH- p = 0.0001, FH+ p = 0.0001) and lower-body strength (FH- p = 0.0009, FH+ p = 0.0003), but did not change metabolic flexibility (p > 0.05) in both groups. Exercise-induced improvements in metabolic outcomes were similar between groups. Conclusions: Insulin sensitivity, metabolic flexibility, aerobic fitness and strength were not compromised by a FH+. Additionally, a FH+ is not a limiting factor for exercise-induced improvements in insulin sensitivity, aerobic fitness, body composition, and strength in normoglycemic young Mexican-American men.